2022
DOI: 10.3390/cancers14225525
|View full text |Cite
|
Sign up to set email alerts
|

Lenvatinib as First-Line Treatment for Unresectable Hepatocellular Carcinoma: A Systematic Review and Meta-Analysis

Abstract: Lenvatinib was approved in 2018 as a first-line treatment for patients with unresectable hepatocellular carcinoma (HCC). This systematic review and meta-analysis aimed to provide the most updated evidence about the efficacy and safety of lenvatinib as a first-line treatment for unresectable HCC. An electronic search of the PubMed database, Web of Science, Embase, and Cochrane Library was undertaken to identify all relevant studies up to May 2022. The pooled effect sizes were calculated based on the random-effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…A meta‐analysis has revealed that LENV has superior antitumor response and survival advantages than sorafenib as a first‐line therapy for advanced/unresectable HCC patients. In addition, LENV showcases competitive therapeutic efficacy with similar incidences of AEs 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta‐analysis has revealed that LENV has superior antitumor response and survival advantages than sorafenib as a first‐line therapy for advanced/unresectable HCC patients. In addition, LENV showcases competitive therapeutic efficacy with similar incidences of AEs 25 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, LENV showcases competitive therapeutic efficacy with similar incidences of AEs. 25 In 2020, a new combination approach of ATE plus BEV was shown to be more beneficial than other first-line drugs due to their favorable safety profiles in advanced HCC patients. 26 ATE/BEV is associated with better PFS, OS, response rate, and preservation of quality of life than sorafenib (IMbrave150).…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…These adverse events may be due to lenvatinib as hypertension, diarrhea and gingival bleeding have been reported as common adverse events in unresectable HCC patients treated with lenvatinib. 26 , 27 A recent meta-analysis showed that lenvatinib-induced hypertension may be associated with better prognosis. 28 Lenvatinib-induced adverse events could be managed through regular monitoring, preventive measures and symptomatic management.…”
Section: Discussionmentioning
confidence: 99%
“…Most frequent adverse events in the different studies with lenvatinib and pembrolizumab 4,6,17,18,19 Lenvatinib in TC17…”
Section: Tablementioning
confidence: 99%